New replacement name for Chinese leafhopper genus Reticulum Dai, Li & Chen, 2006 (Hemiptera: Cicadellidae: Deltocephalinae) - Dai, Wu (Zootaxa, 2009)
Deltocephalinae is the largest and most economically important group of leafhoppers, containing over 6500 described species (Zahniser & Dietrich, 2008). Many undescribed species of Deltocephalinae have been discovered in China. The deltocephaline genus Reticulum was established by Dai, Li and Chen (2006) with the type species R. transvittatum Dai, Li & Chen from China. Dai and Zhang (2008) revised the genus and added two new species. Nevertheless the name Reticulum is preoccupied and was initially introduced by Schröder, Medioli & Scott, 1989 for a genus of the foraminifer Family Komokidae (with the type species Reticulum pingue Schröder, Medioli & Scott, 1989 from Nares Abyssal Plain). Thus, the genus Reticulum Dai, Li & Chen, 2006 is a junior homonym of the genus Reticulum Schröder, Medioli and Scott, 1989. According to Article 60 of the International Code of Zoological Nomenclature, I propose for Reticulum Dai, Li & Chen, 2006 the new replacement name Neoreticulum nom. nov. Accordingly, new combinations are herein proposed for the cicadellid species currently included in this genus: Neoreticulum lanceolatum (Dai & Zhang, 2008), Neoreticulum trispinosum (Dai & Zhang, 2008), and Neoreticulum transvittatum (Dai, Li & Chen, 2006)